1978
DOI: 10.1111/j.1365-2265.1978.tb03569.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Low T3 Syndrome’ in Patients Chronically Treated With an Iodine‐containing Drug, Amiodarone

Abstract: Cardiac patients treated with the iodine-containing drug 'amiodarone' undergo a significant iodine overload which can last for months after the drug has been withdrawn. Some patients develop hyperthyroidism and others hypothyroidism. In the hyper- or hypothyroid patients, the indices of thyroid function are modified as usually observed in these situations. In the patients remaining euthyroid while taking amiodarone or after its withdrawal, but still under its influence as shown by the iodine overload, a 'low-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…The above results confirm previous re ports from this and other laboratories [24][25][26][30][31][32][33][34][35], indicating that serum TT4 and FT4 values are elevated also in euthyroid am iodarone-treated patients. This finding suggests that total TT4 and FT4 measure ments are of limited help in the diagnosis of A11T, which must be based on serum TT3 and FT3 determinations.…”
Section: Serum Thyroid Hormone Concentrationssupporting
confidence: 81%
“…The above results confirm previous re ports from this and other laboratories [24][25][26][30][31][32][33][34][35], indicating that serum TT4 and FT4 values are elevated also in euthyroid am iodarone-treated patients. This finding suggests that total TT4 and FT4 measure ments are of limited help in the diagnosis of A11T, which must be based on serum TT3 and FT3 determinations.…”
Section: Serum Thyroid Hormone Concentrationssupporting
confidence: 81%
“…The elevation of rT3 during amiodarone therapy has been reported, 16,18 which may account for the observed increases in T4 and rT3 on amiodarone. Also, elevation of serum T4 levels during chronic amiodarone therapy may be due to diminished clearance.…”
Section: Amiodarone Withdrawal After Chronic Therapymentioning
confidence: 80%
“…For all 18 patients, the baseline data, including three or more 24- 16, 291 and purchased commercially from LABAZ) was initially administered at a SERUM REVERSE T3 LEVELS AND AMIODARONE/Nademanee et al…”
Section: Design Of the Protocolmentioning
confidence: 99%
“…The reduction in plasma T3 concentra tions produced by long-term amiodarone therapy in the rabbit is approximately 50% [Patterson et al, 1986] and is similar or slightly greater than the reductions in plasma T3 observed with chronic amioda rone therapy in man [Melmed et al, 1981;Jonckheer et al, 1978;Burger et al, 1976;Pritchard et al, 1975]. The development of hypothyroidism by patients receiving chronic amiodarone therapy is rather small [Heger et al, 1981;Rosenbaum et al, 1976] and does not appear to be a requirement for drug efficacy.…”
Section: Role O F Thyroid Hormone In the Pharmacologic Actions O F Ammentioning
confidence: 99%
“…Many of the long-term actions of amioda rone can be mimicked by experimental hy pothyroidism [Freedberg et al, 1970], If amiodarone were to exert its pharmacologic effects via an antagonism of the actions of thyroid hormone, the delayed onset of the therapeutic response as well as the pro longed response observed after withdrawal of the drug could be provided by the pro longed onset and offset of responses to thy roid hormone. The ability of amiodarone to alter plasma concentrations of thyroxine (T4), triiodothyronine (T3), and reverse triiodothyronine (1T3) has been docu mented in man [Burger et al" 1976;Jonckheer et al, 1978;Pritchard et al, 1975], Moreover, amiodarone-induced decreases in plasma concentrations of the most active species, triiodothyronine (T3), could mimic the actions of hypothyroidism, and in part provide for the pharmacologic actions of amiodarone upon cardiac muscle. The ex periments reported here were performed in part to determine if the pharmacologic ac tions of the drug are similar to those pre viously reported with hypothyroidism, and to determine if the pharmacologic actions of long-term amiodarone administration are observed after the administration of triiodothyronine (T3).…”
Section: Introductionmentioning
confidence: 99%